Describing Parasite Biodiversity: The Case of the Helminth Fauna of Wildlife Vertebrates in Mexico - León, Gerardo Pérez-Ponce de; García-Prieto, Luis; Mendoza-Garfias, Berenit (IntechOpen, 2011)
None